Micro-bead injection spectroscopy for label-free automated determination of immunoglobulin G in human serum - Ramos, Inês I. (2017)
Immunoglobulin G (IgG) represents the major fraction of antibodies in healthy adult human serum, and deviations from physiological levels are a generic marker of disease corresponding to different pathologies. Therefore, screening methods for IgG evaluation are a valuable aid to diagnostics. The present work proposes a rapid, automatic, and miniaturized method based on UV-vis micro-bead injection spectroscopy (μ-BIS) for the real-time determination of human serum IgG with label-free detection. Relying on attachment of IgG in rec-protein G immobilized in Sepharose 4B, a bioaffinity column is automatically assembled, where IgG is selectively retained and determined by on-column optical density measurement. A "dilution-and-shoot" approach (50 to 200 times) was implemented without further sample treatment because interferences were flushed out of the column upon sample loading, with minimization of carryover and cross-contamination by automatically discarding the sorbent (0.2 mg) after each determination. No interference from human serum albumin at 60 mg mL-1 in undiluted sample was found. The method allowed IgG determination in the range 100-300 μg mL-1 (corresponding to 5.0-60 mg mL-1 in undiluted samples), with a detection limit of 33 μg mL-1 (1.7 mg mL-1 for samples, dilution factor of 50). RSD values were < 9.4 and < 11.7%, for intra and inter-assay precision, respectively, while recovery values for human serum spiked with IgG at high pathological levels were 97.8-101.4%. Comparison to commercial ELISA kit showed no significant difference for tested samples (n = 8). Moreover, time-to-result decreased from several hours to < 5 min and analysis cost decreased 10 times, showing the potential of the proposed approach as a point-of-care method. Graphical abstract Micro-Bead Injection Spectroscopy method for real time, automated and label-free determination of total serum human Immunoglobulin G (IgG). The method was designed for Lab-on-Valve (LOV) platforms using a miniaturised protein G bioaffinity separative approach. IgG are separated from serum matrix components upon quantification with low non-specific binding in less than 5 min.